Effect of a large dam on malaria risk: The Koka reservoir in Ethiopia - Lautze, Jonathan F.; McCartney, Matthew P.; Kirshen, P.; Olana, D.; Jayasinghe, G.; Spielman, A. (Wiley, 2008)
Objective  To determine whether the Koka water reservoir in the Rift Valley of Ethiopia contributes to the malaria burden in its vicinity.Methods  Frequency of malaria diagnosis in fever clinics was correlated with distance of residence from the margin of the Koka reservoir. Annual as well as seasonal malaria case rates were determined in cohorts residing < 3, 3–6 and 6–9 km from the reservoir. Plasmodium falciparum risk was compared with that of Plasmodium vivax. A multiple variable regression model was used to explore associations between malaria case rates and proximity to the reservoir, controlling for other suspected influences on malaria transmission.Results  Malaria case rates among people living within 3 km of the reservoir are about 1.5 times as great as for those living between 3 and 6 km from the reservoir and 2.3 times as great for those living 6–9 km from the reservoir. Proximity to the reservoir is associated with greater malaria case rates in periods of more intense transmission. Plasmodium falciparum is most prevalent in communities located close to the reservoir and P. vivax in more distant villages. The presence of the reservoir, coupled with inter‐annual climatic variations, explains more than half of the region's variability in malaria case rates.Conclusion  Large water impoundments are likely to exacerbate malaria transmission in malaria‐endemic parts of sub‐Saharan Africa.